Challenges And Opportunities In Joining Campus Teaching Program: A Case Study At English Education Study Program - Nilma Taula’bi’; Shilfani Shilfani; Meliana Datu (Departement of Mathematics Education, 2023)
The aim of this research is to ensure the challenges and opportunities obtained by students who have followed the MBKM program, especially on the teaching campus program that students follow. The researchers conducted qualitative research method. A purposive sampling strategy is used to obtain data from three (3) students in the English education study program. The findings show that students gain opportunities for discipline and responsibility, increase confidence in teaching students, be fluid and creative in the use of learning media, be creative in improving student literacy, make a lesson plan (RPP) and make sketches and issues, build good communication by understanding the character of students, improve communication through discussion in solving a problem, teach directly and cooperate with the other teacher in carrying out the teaching process, obtain value conversion as a result of learning, obtain assistance in cost of living during the implementation of the program, and obtain UKT assistance in the semester during the implementation of the program. In addition, the findings also found the challenges faced: a lack of interest in learning and student enthusiasm for lessons, the skill and character of students that are different surgeries, limited school facilities, a lack of materials and funds that can be taught, miscommunication with the teacher and colleagues participating in the campus program teaching in the field, a less disciplined environment and the absence of the teaching schedule given by the teacher to teach independently in the classroom.